Rheumatology and Therapy
Rheumatology and Therapy is an international, open access, peer-reviewed, rapid publication journal (peer review in 2 weeks, published 3–4 weeks from acceptance). The journal is dedicated to the publication of high-quality preclinical, clinical (all phases), observational, real-world, and health outcomes research around the discovery, development, and use of rheumatologic therapies. Studies relating to diagnosis, pharmacoeconomics, public health, quality of life, and patient care, management, and education are also encouraged. Areas of focus include, but are not limited to, rheumatoid arthritis, gout, gouty arthritis, psoriatic arthritis, osteoarthritis, juvenile idiopathic/rheumatoid arthritis, systemic lupus erythematosus, axial spondyloarthritis, Pompe’s disease, inflammatory joint conditions, musculoskeletal conditions, systemic sclerosis, and fibromyalgia. The journal is of interest to a broad audience of pharmaceutical and healthcare professionals and publishes original research, reviews, case reports, and short communications. The journal appeals to a global audience and receives submissions from all over the world. Articles published in Rheumatology and Therapy may be accompanied by lay-level summaries, to assist patients (and caregivers) in understanding important medical advances. Moving forward from traditional publishing, Rheumatology and Therapy offers a range of additional enhanced features designed to increase visibility, readership, and the educational value of the content. Each paper is accompanied by a bulleted Summary slide, giving a time-efficient overview of the content to a wide readership. Articles also have the option to include various other types of enhanced features including slide sets, videos and animations. All enhanced features are open access and are peer reviewed to the same high standard as the article itself. Rheumatology and Therapy is published under the Creative Commons Attribution-Noncommercial License, which allows users to read, copy, distribute, and make derivative works for non-commercial purposes from the material, as long as the author of the original work is cited. The author assigns the exclusive right to any commercial use of the article to Springer. For more information about the Creative Commons Attribution-Noncommercial License, click here: http://creativecommons.org/licenses/by-nc/4.0. Upon acceptance of your article for publication, you will be required to pay the article processing charge of £250/ €340/ $380 per printed page. This will enable you to keep the copyright; you are simply assigning the exclusive right to any commercial use of the article to Springer. Your article will be immediately and permanently available with open access. The journal will consider fee discounts for developing countries and this is decided on a case by case basis. Peer Review Process Upon submission, manuscripts are assessed by the editorial team to ensure they fit within the aims and scope of the journal and are also checked for plagiarism. All suitable submissions are then subject to a comprehensive double-blind peer review. Reviewers are selected based on their relevant expertise and publication history in the subject area. The journal has an extensive pool of editorial and advisory board members who have been selected to assist with peer review based on the afore-mentioned criteria. At least two extensive reviews are required to make the editorial decision. Where reviewer recommendations are conflicted, the editorial board will be contacted for further advice and a presiding decision. Manuscripts are then either accepted, rejected or authors are required to make major or minor revisions (both reviewer comments and editorial comments may need to be addressed). Once a revised manuscript is re-submitted, it is assessed along with the responses to reviewer comments and if it has been adequately revised it will be accepted for publication. Accepted manuscripts are then copyedited and typeset by the production team before online publication. For more information about the journal, please contact clare.shepherd@springer.com or see the News page for the latest journal offers.